A critical review on multiaxial fatigue models - Paca, Francisco João Bumba (2021)
Most failures in structures mechanical components happen due to fracture and fatigue, which means that mechanical design engineers need to understand the physical phenomena behind these failures. An important aspect that remains to be fully understood is the influence of loading type on the materials fatigue strength. Proportional and nonproportional loads result in different fatigue lives, even when it is applied the same loading amplitudes in both loading conditions. Also, within proportional loads, it can be obtained different fatigue lives according to the ratio between shear and normal stresses. These aspects have been studied over the recent decades and many models have been proposed in literature to overcome these issues, however, a universal model to estimate fatigue strength of materials considering loading effects remains to be reached. In this dissertation, a literature review was carried out focusing on multiaxial fatigue topics, i.e., the review started with the phenomenological characterization of fatigue, passing through critical plane models, cycle counting methods, and ending in fatigue damage monitoring. During the literature review, the stress scale factor (SSF) model, an equivalent shear stress model, raised relevant questions which were studied in the following chapters. This study was conducted using multiaxial fatigue data of the high strength steel 42CrMo4 obtained from literature. These data were originally evaluated and computed at 0° for five multiaxial loading paths, and in this study the analysis was extended to other plane orientations starting from -90° to 90°. The research hypothesis was motivated by the existence of a plan whose orientation would simplify the assessment of the SSF damage map. The ultimate goal would be to estimate SSF damage map based on parameters obtained with simple tests. The actual method to determine the SSF damage map is based on Datafit, a commercial software that contains huge set of multivariable function used to perform regressions of experimental data. To facilitate the regression for a wide range of plane orientations an alternative method to determine the SSF damage map was developed to be later implement in a programming routine. The findings obtained demonstrated that in fact the damage scale does vary with the plane orientation. With regard to the plane in which the damage map was evaluated, i.e., crack initiation plane at -16° obtained with PP45 loading path, the results demonstrated that a good fatigue life results can be estimated from another plane orientation rather than 0°. Moreover, the results of the critical plane models estimate for the orientation of the crack initiation plane at -16° showed some good correlations except the SWT model. Lastly, the new method developed to estimate the SSF damage map was used to estimate the SSF damage map in the plane oriented at -16°, the results obtained were not satisfactory when compared with the result obtained with the SSF damage map estimated using the commercial software Datafit. However, for 0° orientation, the proposed method yields a quite good SSF damage map which predicts fatigue life results better than those obtained using the SSF damage map obtained with Datafit at 0°.